Impact of E-service quality on E-loyalty with the moderating effect of E-satisfaction of youngsters using E-commerce platforms, an empirical evidence from Shopee in Vietnam (International Journal of Scientific Research and Management (IJSRM), 2023)
This study measures the influence of e-service quality on e-satisfaction, thereby affecting the e-loyalty of young people when shopping online on Shopee Vietnam. The purpose of this study is to provide knowledge to better understand the most important aspects of e-service quality that affect youth satisfaction, thereby affecting loyalty. This study uses qualitative research method combined with quantitative research method. The study conducted a survey on 250 users of Shopee e-commerce site. The results show that e-service quality has a significant impact on e-satisfaction in using the Shopee e-commerce platform, and satisfaction has an impact on loyalty. In which, the factor that has the greatest impact on e-satisfaction is Fulfillment.